Mathematical Olympiad issues to identify students' reasoning ability using Polya's model - Mohammad Tohir; Muhasshanah Muhasshanah; Riyan Hidayat; Erik Valentino; Tommy Tanu Wijaya (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This research aims to describe the level of mathematical reasoning ability of students in solving mathematical Olympiad problems based on problem-solving of the Polya model. This study employed descriptive analysis with a qualitative approach. Data were collected by using observation, documentation, and interviews. The study subjects were 27 junior high school students participating in the National Science Competition in Indonesia. Meanwhile, the Miles and Huberman analysis model was used as the data analysis. The results of this study indicated that: (1) the level of students’ mathematical reasoning-ability based on the problem-solving of Polya models in the category of